ANALISIS KEMAMPUAN LITERASI MEMBACA SISWA KELAS IV DI SD NEGERI 54 SELUMA - Wulandari, Meisi Dwi; Febrianti, Adel; Friantary, Heny; Taulani, Andre; Yulizah, Yosi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low reading literacy ability of elementary school students, especially in the aspect of reading comprehension. This study aims to analyze the reading literacy ability of grade IV students at SD Negeri 54 Seluma, identify aspects that have and have not been mastered, and find out the factors that affect them. The research uses a descriptive qualitative approach with data collection techniques in the form of tests, interviews, and documentation. The results of the study show that students' reading literacy skills are in the category of adequate. Students are able to understand the explicit information in the text, but still have difficulty in interpreting the implied meaning and drawing conclusions. Factors that affect include low interest in reading, limited learning media, and conventional learning methods. Therefore, more innovative learning strategies are needed to improve students' reading literacy skills.